Evidence for Recombination Between Feline Panleukopenia Virus and Canine Parvovirus Type 2 - OHSHIMA, Takahisa; MOCHIZUKI, Masami (Journal of Veterinary Medical Science, 2009)
Canine parvovirus type 2 (CPV) is a virulent pathogen that emerged in the late 1970s, probably originating from feline panleukopenia virus (FPLV) or a closely related carnivore parvovirus belonging to the feline parvovirus (FPV) subspecies. In contrast to FPLV, CPV has evolved rapidly since its emergence. The original antigenic type of CPV disappeared more than two decades ago and several new antigenic as well as genetic CPV variants have appeared and spread in the field. Both high mutation rate and positive selection of mutations in the capsid gene appear to be the driving force for such rapid evolution. In addition, genetic recombination has been assessed as a factor in parvovirus evolution. Recently, we provided the first evidence of inter-antigenic type recombination of CPV in nature. Here, an inter-FPV subspecies recombinant was revealed by analyzing the genetic data deposited in databases with several recombination detection programs, and by phylogeny. FPLV strain XJ-1, submitted by Su et al., Harbin, China in 2007 (GenBank accession no. EF988660), was most likely generated by recombination between CPV and FPLV. Its genome was generally composed of the NS1 gene of CPV origin and the VP1 gene of FPLV origin. This is the first demonstration of recombination between different FPV subspecies in nature. Consequently, recombination should be considered as an element in the generation and evolution of parvoviruses of the FPV subspecies.